PERAN ISTRI DALAM UPAYA MENINGKATKAN PEREKONOMIAN RUMAH TANGGA DITINJAU DARI EKONOMI ISLAM - Kaltin; Sri Deti; Kamil (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
This research departs from the phenomenon due to poverty pressure and further development of the economy and technology, at least in the last decade slowly the participation of women in the public sector seems to be increasing. Women are increasingly visible in economic resources that are no less important than men. Thus, the success of a family in forming a prosperous household cannot be separated from the role of a woman who is so big. The aims of this study were to: 1) Analyze the role of the wife in the household economy in the Tebas People's Market, Tebas District, Sambas Regency. 2) Analyzing the role of the wife in an effort to improve the household economy from the perspective of Islamic economics. This research is classified as a qualitative research and case study type. Data collection techniques through observation, interviews and documentation. Data analysis uses an interactive analysis model which includes data reduction, data display, and verification/drawing of conclusions. Based on the results of the discussion, it can be concluded: 1) The role of the wife in improving the economy can already be seen from the role of a woman (housewife in Tebas People's Market) who helps a lot to advance the family economy by taking part in earning a living as a worker. 2) Regarding the Islamic economic review regarding the role and contribution of women in working and increasing family income, respondents have been able to fulfill the Maslahah Dharuriyat, and Hajiyyah levels, while Maslahah Tahsiniyat has not been able to be fulfilled, the work of the female workforce illustrates that by working the wife/housewife participates. feel the struggle of a husband in earning a living in order to be able to create prosperity in the family, because the income earned is also used to meet basic daily needs and also outside basic affairs such as children's education. Keywords: economy, household, islamic, wife role